Granice obowiązywania zasady ignorantia iuris nocet w polskim procesie karnym - Czerniak, Dominika (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2015)
The author analyses how the Roman rule according to which everyone bears negative consequences of ignorance of the law has been applied in criminal procedure from the Code of Criminal Procedure of 1928 to the current regulations. There is no doubt that, given the nature of criminal procedure, an entity cannot be left “to fend for oneself”. In the article the author emphasises the importance of the obligation to inform the participants of the criminal proceedings of their rights and obligations by the authorities of the trial (judge or prosecutor). Consideration is also given to the increase of the scope of information which participants in the criminal proceedings get form the authorities of the trial. Finally, the author points out that the obligation to inform the entity of their rights and obligations in the criminal proceedings also can be considered as an act of loyalty in the criminal procedure.
Keywords: rules in criminal procedure; principle of loyalty to the process; right to information in criminal proceedings; criminal proceedings; procedural guarantees